Morbidity in early childhood: differences between girls and boys under 10 years old. - van den Bosch, W J (1992)
The aim of the study was to investigate the differences in presented morbidity and use of health services among boys and girls in early childhood. The study was performed using data collected by the continuous morbidity registration project of the department of general practice at Nijmegen University. All recorded morbidity, referrals to specialists and admissions to hospitals were recorded by the registration project. The study population included children born in four practices from 1971 to 1984. The children were followed up until the age of five years and if possible until the age of 10 years. The morbidity of the children had been categorized into three levels of seriousness of diagnosis and 15 diagnostic groups as part of the registration project. Boys presented more morbidity than girls in the first years of their lives. For the age group 0-4 years this was true for all levels of seriousness of diagnosis except the most serious. In this younger age group significantly more boys than girls suffered respiratory diseases, behaviour disorders, gastroenteritis and accidents. Girls suffered from more episodes of urinary infection than boys in both age groups. More boys were referred to specialists and admitted to hospital than girls. The findings of this study suggest that not only inborn factors can explain the sex differences in presented morbidity and use of health services in early childhood. In particular, differences between girls and boys in terms of non-serious morbidity and referral and admission rates suggest a different way of handling health problems in boys and girls in early childhood both by parents and doctors.(ABSTRACT TRUNCATED AT 250 WORDS)